Repetition Style in Surah Al-Shu'arÄ - Nur Huda; Aminatuz Zahroh; Ahmad Musonnif Alfi; Mas Tajuddin Ahmad (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2024)
Purpose: This study aims to describe the various styles of repetition and their effects in surah al-Shu'arÄ. Stylistics is a language approach that is used to reveal secrets and understand the contents of the Qur'an, in this case the style of language in surah al-Shu'arÄ. Design/methods/ approach: This research is included in the category of qualitative research using descriptive analytical methods. Qualitative research is a type of research that analyzes descriptive data in the form of speech or writing under study. The analytical descriptive method aims to analyze and describe data about the style of repetition in surah al-Shu'arÄ. In addition, this study also uses the â€œsimakâ€ method with â€œsadapâ€ techniques, which is a technique used to obtain data by â€œsimakâ€ to the use of language in surah al-Shu'arÄ. Repetition is the repetition of sounds, syllables, words or parts of sentences that are considered important to emphasize in an appropriate context. Findings: From this study it can be concluded that in surah al-Shu'arÄ found seven styles of language which are grouped into three stylistic domains, namely three styles of language in the phonological levels (al-mustawÄ al-á¹£awá¹i), two styles of language in the morphological levels (al-mustawÄ al-á¹£arfÄ«), and two styles of language in the syntax levels (al-mustawÄ al-naá¸¥wÄ« al-tarkÄ«bÄ«). This research confirms that repetition as a form of language style is very different from repetition as a form of weakness of writers or authors. Research implication: From this research, it can be seen that there is an implication that repetition in Surah al-Shu'arÄ can add to the treasure or richness of meaning in it, such as at the sound level it will produce assonance and rhyme alliteration, at the morphological level it will focus special attention and at the grammatical level it will reveal epizeuxis. as well as anaphora